Faktor-Faktor Yang Memengaruhi Pendapatan Usaha BARBERSHOP di Kecamatan Banjarmasin Utara - Tambun, Rudi Parluhutan; Syafrudin , Ruddy (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research is conducted to find out determine whether capital, price, location affect the income of barbershop businesses in North Banjarmasin District. The object of this research is 20 barbershop in North Banjarmasin District. The research method used is multiple regression analysis, quantitative descriptive analysis and classical assumptions. The results show that the variables of capital, price and location had a significant effect on the income of barbershop businesses in North Banjarmasin District. The results are indicated by the test results of the coefficient of determination (R2), F test and t test with Multiple Linear Regression. The most dominant factor affecting the income of barbershop business is capital.